The Review of Anti-aging Mechanism of Polyphenols on Caenorhabditis elegans - Liu, Limin; Guo, Peisen; Wang, Peixi; Zheng, Shanqing; Qu, Zhi; Liu, Nan (Frontiers in Bioengineering and Biotechnology, 2021)
Micronutrients extracted from natural plants or made by biological synthesis are widely used in anti-aging researches and applications. Among more than 30 effective anti-aging substances, employing polyphenol organic compounds for modification or delaying of the aging process attracts great interests because of their distinct contribution in the prevention of degenerative diseases such as cardiovascular disease and cancer. There is a profound potential for polyphenol extracts in the research of aging and the related diseases of the elderly. Previous studies have mainly focused on the properties of polyphenols implicated in free radical scavenging; however, the anti-oxidant effect cannot fully elaborate its biological functions, such as neuroprotection, Aβ protein production, ion channel coupling and signal transduction pathways, etc. Caenorhabditis elegans (C. elegans) has been considered as an ideal model organism for exploring the mechanism of anti-aging research and is broadly utilized in screening for natural bioactive substances. In this review, we describe the molecular mechanisms and pathways responsible for the slow-down of aging processes exerted by polyphenols. And we also discuss the possible mechanisms for their anti-oxidant and anti-aging properties in C. elegans from the perspective of different classifications of the specific polyphenols, such as flavonols, anthocyanins, flavan-3-ols, hydroxybenzoic acid, hydroxycinnamic acid, and stilbenes.